THE SCIENCE OF FALAK ON VIRTUAL REALITY - achmad didik mulyadi (Al-Hilal: Journal of Islamic Astronomy, 2020)
In the era of the industrial revolution 4.0, astronomers as well as modern society in general cannot turn away from the reality of virtual life. People get information, read and study any knowledge is very easy because everything is available in their hands. Faced with this condition, what about astronomy scholarship? Amid the assumption that astronomy and experts are very rare. So astronomers are demanded to be able to adapt and develop themselves with 'literacy' technology to be able to package the astronomy knowledge and present its content to the public easily and to construct it in digital form. Why does this virtual reality have to be faced and how to deal with it? Associated with efforts to answer the needs of the public about astronomical scholarship in virtual reality, various innovations and creativity of astronomers emerged in the form of digitizing material, books (books) and astronomical applications. This variety of innovations will increase the interest of millennial students to learn and master it. Through this paper,-some of the digitization pattern-, the author will study it with the content analysis method and describe it descriptively-interpretatively. From the results of studies, the author has led to a conclusion that; the first, found a number of patterns of celestial scientific digitalization; from the side of the content, the digital astronomical material consists of the calculation of qibla direction, prayer time, the beginning of the month and eclipse and the practice of its determination, from the media aspect, the astronomy knowledge is presented through social media, such as facebook, instagram, whatsApp and youtube; through website-based media, such as bimasislam.kemenag.go.id, and if.walisongo.ac.id., in the form of smartphone applications, such as digital falak, mizwandroid, qiblat, usholli and so on. While the design of the presentation is varied, in the form of text, video, images and pdf. The second, each of these patterns has made a valuable contribution to the virtual learning of astronomy for millennial society in the current era of the industrial revolution 4.0.